2010
DOI: 10.1007/s00127-010-0198-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported depression in first-year nursing students in relation to socio-demographic and educational factors: a nationwide cross-sectional study in Sweden

Abstract: Nursing students as a group show high levels of self-reported depression but the prevalence is affected by age with a higher proportion depressed among younger students. Even though older students and those who were parents show less depression, they were more vulnerable to home-college conflicts. As older students and parents constitute a large proportion of nursing students, it is of importance to find ways to lessen the effects of the obstacles they encounter in the education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 71 publications
3
32
3
1
Order By: Relevance
“…Difference in age was not significantly associated with personal experience of mental health problems, in either of the four groups. This contrasts with previous studies in which age differences in prevalence of mental health problems have been found, specifically higher prevalence of mental illness in younger nurses (Morrissy et al, 2013;Arafa et al, 2003;Christensson et al, 2011;Lavoie-Tremblay et al, 2008;Ryan and Quayle, 1999;Letvak et al, 2013).…”
Section: Discussioncontrasting
confidence: 94%
“…Difference in age was not significantly associated with personal experience of mental health problems, in either of the four groups. This contrasts with previous studies in which age differences in prevalence of mental health problems have been found, specifically higher prevalence of mental illness in younger nurses (Morrissy et al, 2013;Arafa et al, 2003;Christensson et al, 2011;Lavoie-Tremblay et al, 2008;Ryan and Quayle, 1999;Letvak et al, 2013).…”
Section: Discussioncontrasting
confidence: 94%
“…The study showed that students with children are 3 times more likely to develop depressive symptoms than those without (OR 3.06 95% CI: 0.96 – 9.74). Other research evidence supports this finding [5,26]. It is evident that being a mother, bearing the responsibilities of motherhood along with those of academic pursuits may lead to exposure to prolonged stress [5,26].…”
Section: Discussionmentioning
confidence: 62%
“…Other research evidence supports this finding [5,26]. It is evident that being a mother, bearing the responsibilities of motherhood along with those of academic pursuits may lead to exposure to prolonged stress [5,26]. Such demands, in conjunction with other stressful life events e.g.…”
Section: Discussionmentioning
confidence: 69%
“…Cross-sectional studies have also been performed with nursing students, indicating that they are at high risk of developing psychological distress (Christensson, Vaez, Dickman, & Runeson, 2011;Jones & Johnston, 2000). Longitudinal studies have confirmed that nursing students' psychological distress increases significantly during their education (Christensson, Runeson, Dickman, & Vaez, 2010;Deary, Watson, & Hogston, 2003;Lo, 2002;Nerdrum, Rustoen, & Ronnestad, 2009;Watson et al, 2009).…”
Section: Psychological Distress Among Nurses and Nursing Studentsmentioning
confidence: 99%